2018
DOI: 10.1029/2018jd028298
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Water‐Heat Exchanges and Inconsistent Surface Temperature Changes at an Elevational Permafrost Site on the Qinghai‐Tibet Plateau

Abstract: Increase of surface temperatures has long been recognized as an unequivocal response to radiative forcing and one of the most important implications for global warming. However, it remains unclear whether the variation of ground surface temperature (GST) and soil temperatures is consistent with simultaneous changes of the near‐surface air and land (or skin) surface temperatures (Ta and LST). In this study, a seven‐year continuous observation of GST, Ta, and surface water and heat exchange was carried out at an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 53 publications
(131 reference statements)
1
33
0
1
Order By: Relevance
“…The insulating effects of snow cover in the winter and vegetation cover in the summer cause a large temperature deviation between ground surface temperature and the near-surface or land surface temperatures. However, previous studies demonstrated that the near-surface air temperature is linearly correlated to the land surface temperature [73,74]. Moreover, the mean annual or freezing and thawing indices of the near-surface are approximately consistent with those of the land surface on the TP [74].…”
Section: Data 231 Modis Lstmentioning
confidence: 66%
“…The insulating effects of snow cover in the winter and vegetation cover in the summer cause a large temperature deviation between ground surface temperature and the near-surface or land surface temperatures. However, previous studies demonstrated that the near-surface air temperature is linearly correlated to the land surface temperature [73,74]. Moreover, the mean annual or freezing and thawing indices of the near-surface are approximately consistent with those of the land surface on the TP [74].…”
Section: Data 231 Modis Lstmentioning
confidence: 66%
“…In this sense, surface characteristics, rather than elevation gradients, are presumed to be primarily associated with the degree of permafrost warming. Detailed studies comparing the changes of different surface temperatures and their effects on the thermal regime of the ground in the context of climate warming are expected in the future …”
Section: Discussionmentioning
confidence: 99%
“…Based on data for 1957-2016, this area had a mean annual air temperature of −3.5 C. 39 Mean annual precipitation was~460 mm during 2011-2016. 39 The permafrost is warm (with mean annual ground temperature [MAGT] of −0.7 C) and thermally unstable, and discontinuous and sporadic in areal extent. 39 Three representative vegetation types (i.e., ASM, AM, and AS) were selected for study in this area.…”
Section: Study Sitementioning
confidence: 99%
“…39 The permafrost is warm (with mean annual ground temperature [MAGT] of −0.7 C) and thermally unstable, and discontinuous and sporadic in areal extent. 39 Three representative vegetation types (i.e., ASM, AM, and AS) were selected for study in this area. These three vegetation types are common, representative, and widespread on the QTP.…”
Section: Study Sitementioning
confidence: 99%